Transactions costs and the relationship between put and call prices - Gould, J.P.; Galai, D. (Journal of Financial Economics, 1974)
The relationship between prices of puts and calls on securities that is suggested by the theory of efficient markets is developed and empirically tested in this paper. We find that the basic model is not supported unless rather large transactions costs are included. Moreover, the transactions costs that must be assumed to make the model consistent with the data are so large as to raise troublesome questions as to whether there were unexploited profit opportunities in the options market at least during the 1967–1969 period. We also find that similar deviations from the efficient market hypothesis have shown up in related work by other researchers but that their explanations of these results appear to be incorrect on theoretical grounds or too sanguine.